Pengembangan Komoditas Pertanian Unggulan di Wilayah Perbatasan Bengkayang Mendukung Pengembangan Lumbung Pangan - Joko Mulyono (TATALOKA, 2020)
Agricultural productivity in the border region of Bengkayang Regency is low, on one side the area of agricultural land is quite extensive (89.23%) coupled with a population density of only 44 people/km2. The research objective was to determine the leading agricultural commodities in the border region of Bengkayang Regency, West Kalimantan Province to support the development of a national food barn. This study uses secondary data covering data on crops harvest area, horticulture crop production, plantation production, and livestock populations in 2011-2015 obtained from the Bengkayang Regency Central Statistics Agency (BPS), West Kalimantan. The data is analyzed by analysis of Location Quotient (LQ) and Shift Share Analysis (SSA). The results of the study showed that oil palm was the plantation’s leading commodities in the border region of Jagoi Babang Subdistrict and pepper in Siding SubDistrict. Cows, pigs, and ducks are the leading commodities of livestock in the border region of Jagoi Babang Subdistrict and ducks in Siding Subdistrict.